Integrasi Metode SAW dalam Sistem Informasi Inventaris untuk Mitigasi Risiko Stockout pada Industri Jasa Hiburan - Aris Setia Hermawan; Donna Setiawati; Ari Pantjarani; Fera Tri Wulandari (JITU, 2026)
Operational management in the entertainment industry, such as Kingstar Family Karaoke, faces complex challenges in determining procurement priorities due to uncertain operational fluctuations. This uncertainty often creates the risk of stockpiling or, conversely, stockouts, which directly impact the quality of customer service. This study aims to optimize the procurement decision-making process by integrating the Simple Additive Weighting (SAW) algorithm into an inventory information system. The research methodology follows the Systems Development Life Cycle (SDLC) framework with a Rapid Application Design (RAD) approach, which includes requirements analysis, system design, and software-based implementation. The SAW algorithm is applied to objectively balance the parameters of ending stock, sales level, and purchase price through a process of normalization and preference weighting. The test results show that the integration of the SAW method is able to provide accurate procurement priority recommendations, thereby assisting management in making more measured managerial decisions and mitigating the risk of operational losses.